Effects of Health Insurance on Quality of Care in Low-Income Countries: A Systematic Review - Doris Osei Afriyie; Doris Osei Afriyie; Brendan Kwesiga; Grace Achungura; Fabrizio Tediosi; Fabrizio Tediosi; Günther Fink; Günther Fink (Frontiers Media S.A., 2023)
Objectives: To evaluate the effectiveness of health insurance on quality of care in low-income countries (LICs).Methods: We conducted a systematic review following PRISMA guidelines. We searched seven databases for studies published between 2010 and August 2022. We included studies that evaluated the effects of health insurance on quality of care in LICs using randomized experiments or quasi-experimental study designs. Study outcomes were classified using the Donabedian framework.Results: We included 15 studies out of the 6,129 identified. Available evidence seems to suggest that health insurance has limited effects on structural quality, and its effects on the process of care remain mixed. At the population level, health insurance is linked to improved anthropometric measures for children and biomarkers such as blood pressure and hemoglobin levels.Conclusion: Based on the currently available evidence, it appears that health insurance in LICs has limited effects on the quality of care. Further studies are required to delve into the mechanisms that underlie the impact of health insurance on the quality of care and identify the most effective strategies to ensure quality within insurance programs.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=219984, identifier PROSPERO CRD42020219984